O DIREITO HUMANO À NACIONALIDADE: A APATRIDIA COMO UMA VIOLAÇÃO DE DIREITOS HUMANOS - ARIADNE CELINNE DE SOUZA E SILVA (2022)
This dissertation has as its object the study of the right to nationality from a human rights perspective, in particular the interpretation given to this right by the Inter-American Court of Human Rights (IA Court HR) and specifically, the study of cases of statelessness in the Dominican Republic. The Dominican Republic is the country with the largest number of stateless people in the Americas, according to data from the United Nations High Commission for Refugees (UNHCR). The right to nationality is a universal human right, as the core of human dignity. It is not limited to the domestic law of a State, being ensured by numerous international human rights instruments. Statelessness, the condition of not having a nationality recognized by any State, is a violation of a person’s human right, as there is no record of its existence, of belonging to humanity. Statelessness can be correlated to Goal 16 of the Sustainable Development Goals 16.9: “By 2030, provide legal identity for all, including birth registration”. It is qualitative research, using the deductive, analytical method, regarding data collection, bibliographical and documental review, as a reference the case study Yean and Bosico vs. Dominican Republic. Its general objective is to analyze the human right to nationality and the duty to eradicate statelessness in the context of the Global Human Rights System and the Inter-American Human Rights System. As specific objectives: examine the flexibility of state sovereignty in defining nationality standards in its territory, when these could result in statelessness; contextualize the human right to nationality in the face of migratory flows in the twenty-first century; analyze the case study Yean and Bosico vs. Dominican Republic and the consequences of state accountability for non-recognition of the right to nationality in the country, based on the principle of full compliance of the sentence and the conventionality control of internal rules by State Parties. Based on the case study the following questions arise: Has the Dominican Republic exercised conventionality control in its territory? Has the country adopted the interpretation established by the IA Court HR? It is noted that statelessness is a problem that affects millions of people and sometimes stems from mistaken legislations from the person’s State of birth. The Dominican Republic State’s dubious posture in relation to the Inter-American Human Rights System is observed, with partial commitment to the American Convention on Human Rights (ACHR), as it maintains a discriminatory policy in relation to the children of Haitian migrants, alleging the prevalence of state sovereignty to determine the nationals of its territory.